Pengaruh Praktik Kesetaraan Gender dan Status Gizi (IMT/U) Terhadap Usia Menarche pada Remaja Putri di Yayasan Perguruan Ki Hajar Dewantara - Asrika Sari Harahap (Jurnal Sehat Mandiri, 2020)
Menarche is a menstrual event that occurs for the first time in women. Each adolescent has a variety of ages in reaching sexual maturity. Many factors cause differences in the age of menarche, including nutritional status. This study aims to analyze the effect of gender equality practices and nutritional status (BMI / U) on the age of menarche in young women of Yayasan Perguruan Ki Hajar Dewantara. This type of research is observational analytic with a cross-sectional study design. The data analysis method is path analysis. The population was 784 female students. The sampling technique used simple random sampling, namely 58 students. The results of the study had no direct effect on nutritional status (BMI / U) on the age of menarche. There is a direct influence of intake on nutritional status, namely ρ-value = 0.049 <0.05 and gender equality practice on intake, namely the path coefficient value that ρ-value = 0.003 <0.05. The conclusion is that there is an indirect effect of gender equality practices on status nutrition and gender equality practice on the age of menarche with beta value on the indirect effect is greater than the beta value on the direct effect. It is recommended to further increase knowledge of gender equality practices, growth and development of young women about the age of menarche and improve diet and see the nutritional status of young women with counseling.